Journal of Laboratory Medicine : Official Journal of the German Society of Clinical Chemistry and Laboratory Medicine (De Gruyter, 1977)
NEW: OPEN ACCESS! The Journal of Laboratory Medicine represents the broad aspects of integrating clinical chemistry and laboratory medicine. It focusses on the diagnostic aspects of the clinical laboratory and covers technical and educational topics. Specialized in the publication of review articles on clinical, methodological and pathogenic aspects of laboratory diagnostics. It also accepts research articles, case reports, letters to the editor.